Holiday affair - Hartman, Don, 1900-1958.; Lennart, Isobel; Mitchum, Robert; Leigh, Janet; Corey, Wendell, 1914-1968.; Gebert, Gordon; Barnett, Griff; Dale, Esther, 1885-1961.; O'Neil, Henry; Morgan, Harry, 1915-2011.; Krasner, Milton; Marker, Harry; et al. (Burbank, CA Turner Entertainment Warner Bros. Entertainment, 2008)
A recently-unemployed man is helping a child who'd otherwise find disappointment under the Christmas tree. The boy's war-widowed mom notes the gesture, and she's drawn to the handsome stranger--but could she possibly choose a man without a job to the moneyed attorney she's been seeing?
Originally released as a motion picture in 1949.
Based on the story: Christmas gift by John D. Weaver.
Director of photography, Milton Krasner ; editor, Harry Marker ; music, Roy Webb.
Robert Mitchum, Janet Leigh, Wendell Corey, Gordon Gebert, Griff Barnett, Esther Dale, Henry O'Neil, Henry Morgan.
MPAA rating: not rated.
DVD; NTSC; standard format; Dolby Digital mono.
Keywords: Christmas plays; Man-woman relationships -- Drama; Triangles (Interpersonal relations) -- Drama; War widows -- Drama; Christmas plays; Video recordings with French language options; Film adaptations; Christmas films; Drama; Feature films; Fiction films; Romantic comedy films; Video recordings for the hearing impaired